MILLIY SPORT TURLARIGA OID ATAMALAR POLISEMIYASI - Babayarov, M.X. (SCIENCE and SOCIETY, 2024)
This article talks about the terms used in national sports and the phenomenon of polysemy that occurs in them. It should be noted that the ambiguous aspect of words in national sports is determined based on the linguistic and cultural characteristics of each nation. In determining the phenomenon of polysemy in terms, it is appropriate to clarify the national culture of nations, national sports games and related terms and analyze them from a linguistic world view.